Voice Outcomes After Endoscopic Treatment of Laryngotracheal Stenosis. (March 2015) - Hatcher, Jeanne L.; Dao, Ashley M.; Simpson, C. Blake
Objective: This study aimed to assess vocal disability in patients with laryngotracheal stenosis who are managed with endoscopic surgery, comparing patients with posterior glottic stenosis (PGS) to those with subglottic or tracheal stenosis (SGS/TS). Methods: Patients who underwent endoscopic treatment for laryngotracheal stenosis with voice outcomes data from 2005 to 2013 were studied. The mean Voice Handicap Index–10 (VHI-10) was compared over the study period. Of those with SGS/TS, the distance from the vocal folds to the proximal portion of the stenosis was obtained and compared to VHI-10. Results: Forty-four patients met inclusion criteria. The mean VHI-10 for all patients was 14.6. Fifty percent were dysphonic (VHI-10 > 11). The mean VHI-10 for PGS patients was 22.4, and for SGS/TS patients, 10.9 ( P = .004). Of those with PGS, 78.6% were dysphonic compared to only 36.7% of those with SGS/TS. Voice Handicap Index–10 improved from 14.1 for those with proximal stenosis to 4 for those with stenosis more than 2 cm distal to the vocal folds. Conclusion: Following endoscopic management of stenosis, those with PGS have poorer voice outcomes compared to those with SGS/TS. The majority of those with SGS/TS are not dysphonic. Vocal outcomes are greatest for those with stenosis beginning at least 2 cm distal to the vocal folds.